Hip- and back-protectors in sports and everyday life - Effective protection? - Jöllenbeck, T.; Schönle, C.; Pietschmann, J.; Glage, D. (ISBS - Conference Proceedings Archive (Konstanz), 2015)
Hip and back protectors are recommended to reduce impact forces when falling in sports or everyday life. This study analyzed the shock-reducing effect of 29 different hip and back protectors using a drop test and a Kistler force plate. Our results showed large differences between the single protectors. Measured peak forces often and quickly exceeded the supposed limit of bone fracture strength. Therefore sufficient safety does not seem to exist yet and protectors must not be overestimated in their protection potential. In our opinion protectors should have a certain thickness preferably a combination of hardshell and viscoelastic material. Hip protectors for sports still show large deficits. Back protectors only protect against direct contusion but not against axial compressions or cervical spine.